The Effect of Using Word Family Game on The Vocabulary Mastery of The Fifth Grade Students at SD Negeri 1 Astina in Academic Years of 2017/2018 - Ni Komang Amelia Kartadi (Universitas Pendidikan Ganesha, 2017)
This study aimed at investigating of the effect of using word family game committed by the fifth grade student in SD Negeri 1 Astina in mastering the English vocabulary. This study was True-Experimental with post-test only control group design. The population was 59 students of the fifth grade and the sample was selected by using cluster random sampling. The sample of this research study was 22 students in 5A as an Experimental Group while 22 students in 5B as a Control Group. The experimental group was taught by using Word Family Game and control group was taught without using Word Family Game. The data was analyzed descriptively and inferentially through SPSS 16.0 Program. Descriptively, the students in experimental group were achieved better than the students in control group. It was proven by the result of the mean score of the experimental group was 90.45, while the mean score of control group was 83.18. The result of the t-test also showed that the score of the (tobs) was 3.393 which the score of (tcv) was 1.682 which based on the degree of freedom was 42. It showed that the (tobs) > (tcv), where: 3.393 > 1.682. It could be concluded that the word family game had a significant effect on the students’ vocabulary mastery rather than using conventional teaching.